Adapting A Family-Based HIV Prevention Program for Homeless Youth and Their Families: The HOPE (HIV prevention Outreach for Parents and Early adolescents) Family Program - Messam, Taiwanna (2010)
As rates of HIV infection increase in adolescents, it is important to provide prevention programs targeting this population. Homeless adolescents living with their families in shelters are at greater risk of participating in risky sexual behavior and incurring negative health outcomes. A family based HIV-prevention pilot study was conducted with eight homeless families in a New York City shelter to explore: 1) the perceived impact of family communication, parental monitoring, family understanding of puberty, STD's and HIV on preventing risky behavior for the participating youth, and 2) the feasibility of conducting such a program within the shelter system. Qualitative and quantitative results indicate increased family communication, parental monitoring and decreased parental depressive symptoms.